Economic, Social and Environmental Aspets for the Promotion of Cultural Heritage in the Balkans - Gavra, Eleni G.; Gkioufi, Kleoniki (European Journal of Economics and Business Studies, 2019)
This paper attempts an exploration of economic, social and environmental issues that are related to the promotion of cultural heritage of reference areas in the Balkans. The assessment of the value of cultural heritage contributes to the proper management of cultural identity and hence to the promotion of the image of a region. The enhancement and promotion of cultural identity, focusing on sustainable development, is a key issue in urban planning. In theoretical level it is analyzed the economic, social and environmental aspects of an area that affect the promotion of the cultural reserve and are related to the promotion of the area image. The socio-economic conditions, quality of life, historical traditions and aesthetic values directly affect the cultural environment as an extension of the global environmental system. Contemporary planning policies include practices for the protection and promotion of cultural assets through innovative applications, fulfilling technological requirements. The importance and wealth of cultural reserve in the Balkans is particularly demonstrated by the large number of monuments and sites classified as "World Heritage Sites" by UNESCO, contributing to the promotion of the cultural image of the region, through practical effects. Through specific reference examples, in this paper, we present the new urban policies that enhance the image of the Balkans, highlighting their characteristics. The objective is to evaluate/assess the implementation of economic, social and environmental aspects in planning as an anticipated public benefit in cultural promotion of areas in the Balkans.
Keywords: Balkans, cultural heritage, management, promotion, strategic planning